A Theoretical Review of General Linguistic on Linguistic Phenomena in Arabic Language - Afnan Arummi (Arabic Literature Department, 2020)
This paper aims to describe linguistic phenomena in Arabic as seen from general linguistic theories. Based on the universal nature of language, the unique of a language system can be analyzed using external approaches outside of it. By this comparative method, novelty can be found frequently and encourage the development of a theory. The method used is descriptive and comparative. Descriptive methods are used to describe general linguistic theories. The comparative method is used to find the similarities of the two linguistic systems, especially at the syntactic and morphological levels. Several conclusions were drawn. First, at the syntactic level, Arabic has a system that is not much different from the system in general linguistics. Several syntactic theories in general linguistics such as transitivity theory, X-Bar Theory, Theta Theory and Case Theory can be found in Arabic equivalent. Second, in its morphological system, Arabic also has the same word formation processes such as Affixation, Acronym, Conversion, Back Formation, Clipping, Blending, Compounding, Borrowing, and Coinage.